Lyricism, Sensibility, and Morality in the Enlightenment Inspiration of Cienfuegos’ Tragedies - Rinaldo FROLDI (Cuadernos Dieciochistas)
This article studies cienfuegos’ tragedies (Idomeneo, Zoraida, La condesa de Castilla, Pítaco) as the dramatic continuation of certain poetic and spiritual anxieties that the poet underwent during the period he spent in Salamanca. themes that appeared earlier in his poems now reappear in the tragedies (written while he lived in Madrid) and are placed in the mouths of characters who express on stage their deepest longings and concerns: the humanitarian impulse, faith in equality and fraternity, life in harmony with nature. this reflects a sensibility clearly in synch with enlightenment thought, and should not be associated with Romanticism.